Whose stories are told and who is made responsible? Human-interest framing in health journalism in Norway, Spain, the U.K. and the U.S. (January 2023) - Figenschou, Tine Ustad; Thorbjørnsrud, Kjersti; Hallin, Daniel C
Human-interest narratives are journalistic tools to captivate and engage the audience, influence public opinion and bring revenue to media organizations. This paper analyses how human-interest narratives are used in contemporary health journalism across media systems and health systems. Based on a comparative content analysis of Norwegian, Spanish, U.K. and U.S. newspapers (2016–2017), it studies how human-interest stories are contextualized, health problems explained and responsibility attributed. The article reveals a complex picture of the role of human-interest stories in health coverage. In line with expectations, the study finds that human-interest stories do tend to emphasize individual biomedical treatment of illness and to privilege idealized victims who fit the routines of dominant media dramaturgy. In contrast to theories that consider personalization of news as an individualization of responsibility and dumbing down of public debate, however, the study finds that human-interest narratives are also used to explain health as a structural phenomenon and a collective responsibility, appealing to political intervention and accountability of health authorities. Such claims are more prominent in European human-interest health stories and less frequent in the more strongly commercialized U.S. health and media system.